The determinant is found by the formula ad-cb
where the letters are: a and b is the top row and c and d is the bottom row
so ad = 12*2 and cb = -6*0
12x2 = 24
-6x0 =0
24-0 = 24
the determinant = 24
Step-by-step explanation:
Remember that the sum of angles on a straight line are supplementary. (180°)
Therefore 3x + 2 + 6x - 20 = 180.
=> 9x - 18 = 180
=> 9x = 198
=> x = 22.
ANSWER
The radius is 4
EXPLANATION
The given equation is:
![{x}^{2} + {y}^{2} - 10y + 6x + 18 = 0](https://tex.z-dn.net/?f=%20%7Bx%7D%5E%7B2%7D%20%20%2B%20%20%7By%7D%5E%7B2%7D%20%20-%2010y%20%2B%206x%20%2B%2018%20%3D%200)
We complete the square to get the expression in standard form:
![{x}^{2} + 6x + {y}^{2} - 10y + 18 = 0](https://tex.z-dn.net/?f=%7Bx%7D%5E%7B2%7D%20%20%2B%206x%20%2B%20%20%7By%7D%5E%7B2%7D%20%20-%2010y%20%20%2B%2018%20%3D%200)
![{x}^{2} + 6x + 9 + {y}^{2} - 10y + 25 = - 18 + 9 + 25](https://tex.z-dn.net/?f=%7Bx%7D%5E%7B2%7D%20%20%2B%206x%20%2B%20%209%20%2B%20%7By%7D%5E%7B2%7D%20%20-%2010y%20%20%2B%2025%20%20%3D%20%20-%2018%20%2B%209%20%2B%2025)
We factor using perfect squares to get:
![{(x + 3)}^{2} + {(y - 5)}^{2} = 16](https://tex.z-dn.net/?f=%7B%28x%20%2B%203%29%7D%5E%7B2%7D%20%20%2B%20%20%7B%28y%20-%205%29%7D%5E%7B2%7D%20%3D%20%2016)
This implies that,
![{(x + 3)}^{2} + {(y - 5)}^{2} = {4}^{2}](https://tex.z-dn.net/?f=%7B%28x%20%2B%203%29%7D%5E%7B2%7D%20%20%2B%20%20%7B%28y%20-%205%29%7D%5E%7B2%7D%20%3D%20%20%20%7B4%7D%5E%7B2%7D%20)
Comparing to
![{(x - h)}^{2} + {(y - k)}^{2} = {r}^{2}](https://tex.z-dn.net/?f=%7B%28x%20%20-%20h%29%7D%5E%7B2%7D%20%20%2B%20%20%7B%28y%20-%20k%29%7D%5E%7B2%7D%20%3D%20%20%20%7Br%7D%5E%7B2%7D%20)
The radius is r=4
Answer:
The second answer. If I got it wrong tried my best
Step-by-step explanation:
brainliest